Desenvolvimento de nanofibras de policaprolactona incorporadas com nanopartículas de óxido de zinco para encapsulamento do etexilato de dabigatrana - Flávia Gontijo da Silva (2019)
Cardiovascular diseases are the leading cause of death in the world. The main treatments for these disorders involve the use of cardiovascular implants and anticoagulants. In this work, a new system for the encapsulation of dabigatran etexilate (DBG), based on polycaprolactone nanofibers (PCL) produced by electrospinning was proposed. In addition, zinc oxide (ZnO) nanoparticles produced by the coprecipitation and hydrothermal methods were incorporated into the nanofibers. Electron microscopy showed that both methods led to the formation of ZnO nanoparticles in the Wurzite form with diameters varying from 33 to 48 nm and uniaxial nanofibers with diameters of 225 to 350 nm. Thermal analysis of the materials showed that the nanofibres are more thermally stable than the pure drug and the contact angle results showed that the drug increases the hydrophilicity of PCL nanofibers. Quantitative studies showed that the electrospinning process led to a drug loading of about 85% and that the drug release in aqueous media occurred by diffusion of the DBG from the polymer matrix. Cell viability and hemocompatibility tests indicated that the nanofibers containing the DBG are non-cytotoxic and do not cause hemolysis or blood coagulation.